The Impact of Fluoroscopy During Percutaneous Nerve Evaluation on Subsequent Implantation of a Sacral Neuromodulator Among Women With Pelvic Floor Disorders: A Randomized, Noninferiority Trial. Issue 8 (4th May 2020) - Gupta, Ankita; Kinman, Casey; Hobson, Deslyn T.G.; Meriwether, Kate V.; Gaskins, Jeremy T.; Uddin, Md. Nazir; Stewart, J. Ryan; Francis, Sean L.
Abstract : Objectives: To evaluate whether percutaneous nerve evaluation (PNE) without fluoroscopy is inferior to fluoroscopy use in women undergoing trials of sacral neuromodulation (SNM) for pelvic floor disorders (PFDs). Materials and Methods: In an unblinded noninferiority trial, women undergoing PNE were randomized to fluoroscopy or no fluoroscopy. The primary outcome was "success" and defined as implantation of the permanent SNM device within three months of PNE. At an expected 40% success and a 30% noninferiority threshold, 33 participants in each group were needed for 80% power ( α = 0.05). Univariate analyses and a logistic regression model adjusting for univariate variables associated with the primary outcome were performed. Results: From April 2016 to December 2018, 74 participants underwent PNE of which 36 underwent PNE with fluoroscopy and 38 without. The fluoroscopy group had less baseline mean daily voids compared to the no fluoroscopy group (10.79 ± 6.48 vs. 16.21 ± 10.05, p = 0.01). PNE performed without fluoroscopy had similar success (18/38, 47.4%) compared to fluoroscopy (21/36, 58.3%), meeting our noninferiority definition (difference 10.9%, 90% CI −8% to 30%, p = 0.049). In a logistic regression model adjusting for age, Charlson comorbidity index, stage of prolapse, and number of baseline voids per day, trial success was still similar between the two groups (adjOR 1.82, 95% CI 0.52 to 6.94, p = 0.36). Conclusions: PNE performed without fluoroscopy is noninferior to PNE with fluoroscopy use for the outcome of SNM device implantation within three months among women undergoing therapy for PFDs.